Putative prophages related to lytic tailless marine dsDNA phage PM2 are widespread in the genomes of aquatic bacteria - Krupovič, Mart (BioMed Central, 2007)
BACKGROUND: The origin and evolution of viruses is currently a heavily discussed issue. One element in this discussion is the innate viral "self" concept, which suggests that viral structures and functions can be divided into two categories. The first category consists of genetic determinants that are inherited from a viral ancestor and encode the viral "self". The second group consists of another set of structures and functions, the "nonself", which is interchangeable between different viruses and can be obtained via lateral gene transfer. Comparing the structures and sequences of the "self" elements, we have proposed that viruses can be grouped into lineages regardless of which domain of life (bacteria, archaea, eukarya) they infect. It has also been suggested that viruses are ancient and possibly predate modern cells. RESULTS: Here we identified thirteen putative prophages (viral genomes integrated into bacterial chromosome) closely related to the virulent icosahedral tailless lipid-containing bacteriophage PM2. Using the comparative genomics approach, we present evidence to support the viral "self" hypothesis and divide genes of the bacteriophage PM2 and related prophages into "self" and "nonself" categories. CONCLUSION: We show here that the previously proposed most conserved viral "self" determinants, the major coat protein and the packaging ATPase, were the only proteins that could be recognized in all detected corticoviral elements. We also argue here that the genes needed for viral genome replication, as well as for host cell lysis, belong to the "nonself" category of genes. Furthermore, we suggest that abundance of PM2-like viruses in the aquatic environment as well as their importance in the ecology of aquatic microorganisms might have been underestimated.